Composition and Distribution Patterns of Seagrass in the Gulf of Tomini - Ferdi Kurniawan Mohamad; Faizal Kasim; Miftahul Khair Kadim (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the composition and distribution patterns of seagrass species in the Gulf of Tomini, Tabulo Selatan Village and Keramat Village, Mananggu District, Boalemo Regency. This research was conducted for 3 months starting from June 2017 until August 2017. The method used was the line transect method at 2 village locations, each with 3 stations. The results showed that the composition of seagrass species at the study site consisted of seagrass Cymodocea serrulata, Cymodocea rotundata, Enhalus acoroides, Syringodium isoetifolium, Thalassia hemprichii and Halophila ovalis. Seagrass distribution patterns are included in the random and cluster categories.